Outcomes of a fatigue management intervention for people with post COVID-19 condition. - Stapleton, Tadhg; Connolly, Deirdre; Bannan, Ciaran; Kent, Brian (My University, 2024)
Objective Fatigue is identified as one of the most prevalent and persistent problems reported by people with post COVID-19 condition that negatively impacts on everyday living and resumption of pre-COVID-19 lifestyle. A pilot occupational therapy fatigue management intervention was designed for patients presenting with post COVID-19 condition fatigue. Design A retrospective analysis was carried out following the delivery of the fatigue management intervention. Self-reported measures of fatigue, wellbeing, and health status were taken at baseline and repeated at two weeks post intervention. Baseline and post intervention scores were compared using nonparametric analysis. Results Sixty participants (73% female), median age 50.5 years (range 17 to 74), 93% reporting symptoms persisting for 12 weeks or longer, completed the fatigue management intervention. All participants reported moderate to severe fatigue impacting on everyday activity at baseline. The greatest impact of fatigue was on engagement in leisure and work activity. Statistically significant improvement in fatigue (p<0.001), wellbeing (P<0.001) and health status (P<0.001) were noted following the intervention. Conclusions Findings indicate the potential of occupational therapy fatigue management interventions to enable self management strategies and reduce the negative impact of fatigue among people with post COVID-19 condition.
PUBLISHED
Keywords: Post COVID-19 condition; Fatigue management; Self management; Occupational therapy; Immunology, Inflammation & Infection; Health outcomes; Infectious diseases; Chronic Health Condition